1987
DOI: 10.1093/carcin/8.9.1295
|View full text |Cite
|
Sign up to set email alerts
|

Response of mammalian ADP-ribosyl transferase to lymphocyte stimulation, mutagen treatment and cell cycling

Abstract: The inhibitors of the nuclear enzyme ADP-ribosyl transferase (ADPRT) had been shown to block the stimulation of quiescent lymphocytes with mitogens suggesting the involvement of the enzyme in the control of gene expression and cell differentiation. By means of the activity-gel assay we have analysed the intensity and the molecular mass of the catalytic bands of the enzyme at early and late times after stimulation of human lymphocytes by phytohemagglutinin. We observed that the increase in the activity of ADPRT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…This finding is in accordance with the observation that there are no DNA SB, requiring the intervention of ADPRT-related repair mechanisms, in quiescent lymphocytes [17]. ADPRT is induced at an early stage during mitogen-stimulated lymphocyte cultures [10], however its activity reaches maximum at around the 48-72 h [6,8]; this observation also supports the view that ADPRT is not required for early DNA repair. It has been suggested that ADPRT carries out other functions, probably related to specific changes in the chromatin structure [33][34][35].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding is in accordance with the observation that there are no DNA SB, requiring the intervention of ADPRT-related repair mechanisms, in quiescent lymphocytes [17]. ADPRT is induced at an early stage during mitogen-stimulated lymphocyte cultures [10], however its activity reaches maximum at around the 48-72 h [6,8]; this observation also supports the view that ADPRT is not required for early DNA repair. It has been suggested that ADPRT carries out other functions, probably related to specific changes in the chromatin structure [33][34][35].…”
Section: Discussionsupporting
confidence: 90%
“…Although the presence of DNA strand breaks (SB) appears to be a prerequisite for ADPRT activation, the role of the enzyme in DNA repair is still poorly understood [2][3][4]. Moreover, ADPRT activity has been found to increase with cell cycle progression [5][6][7][8][9][10]; this suggests that the enzyme also plays a role in physiological processes other than repair.…”
Section: Introductionmentioning
confidence: 99%
“…The difference between cycling versus resting T cells has been recently also shown by effect of the betainterferon, present in cycling T cells but not in resting T cells [Cooper et al, 2004]. Moreover expression of particular genes was shown to be cell cycle dependent, e.g., the link between ATR and p53 genes was present in cycling normal lymphocytes but absent in resting and malignant lymphocytes [Jones et al, 2004a,b] and similar effect was observed for DNA topoisomerase I [Bruno et al, 1992], ADP-ribosyl transferase [Scovassi et al, 1987], and nuclear antigen p105 [Clevenger et al, 1987].…”
mentioning
confidence: 83%
“…The protocol implies SDS ± PAGE, in situ renaturation of proteins, incubation of the gel with 32 P-NAD, removal of non-incorporated substrate and autoradiography. 52,53 The radioactive band at 116 KDa represents automodified PARP.…”
Section: Analysis Of Parp Proteolysis and Autoribosylationmentioning
confidence: 99%